2004
DOI: 10.1111/j.1550-7408.2004.tb00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible UV Inactivation of Cryptosporidium spp. Despite the Presence of UV Repair Genes1

Abstract: Ultraviolet light is being considered as a disinfectant by the water industry because it appears to be very effective for inactivating pathogens, including Cryptosporidium parvum. However, many organisms have mechanisms for repairing ultraviolet light-induced DNA damage, which may limit the utility of this disinfection technology. Inactivation of C. parvum was assessed by measuring infectivity in cells of the human ileocecal adenocarcinoma HCT-8 cell line, with an assay targeting a heat shock protein gene and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 30 publications
5
33
0
Order By: Relevance
“…Previous studies have shown that C. parvum oocysts can be inactivated by low (Ͻ10-mJ ⅐ cm Ϫ2 ) doses of UV light using low-or medium-pressure UV lamps (7,16,18,22). We observed nuclear, anti-TD binding in oocysts irradiated at 40, 20, and 10 mJ ⅐ cm Ϫ2 but not in oocysts irradiated at Ͻ10 mJ ⅐ cm Ϫ2 .…”
Section: -Mj ⅐ CMmentioning
confidence: 49%
See 3 more Smart Citations
“…Previous studies have shown that C. parvum oocysts can be inactivated by low (Ͻ10-mJ ⅐ cm Ϫ2 ) doses of UV light using low-or medium-pressure UV lamps (7,16,18,22). We observed nuclear, anti-TD binding in oocysts irradiated at 40, 20, and 10 mJ ⅐ cm Ϫ2 but not in oocysts irradiated at Ͻ10 mJ ⅐ cm Ϫ2 .…”
Section: -Mj ⅐ CMmentioning
confidence: 49%
“…TDs are common forms of CPD produced in cells when UV light is absorbed by the double bond in the thymine base in a DNA molecule, opening the bond and allowing it to react with the adjacent thymine base, forming a tight four-member ring (12). UV irradiation of C. parvum oocysts also produces CPD, and UV inactivation of C. parvum and C. hominis is irreversible, despite the presence of UV repair genes (10,16,18,19). An assay that can detect the presence of TD following UV inactivation in individual waterborne oocysts would prove beneficial to the water industry, public health professionals, and government regulators.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infectivity or viability of Cryptosporidium oocysts has been evaluated by several molecular, culture or infectivity assays such as: (i) evaluation of comparative infectivity in CD1 mice and in cell cultures using RT-PCR detection assay targeting hsp70 gene mRNA (Rochelle et al, 2002(Rochelle et al, , 2004, (ii) evaluation of infectivity in HC8 cells using qPCR targeting the 18S rRNA gene (Garvey et al, 2010), (iii) cell culture (CC)-PCR assay targeting hsp70 DNA (Aboytes et al, 2004), and (iv) CC-IFA assay on oocysts recovered by USEPA method 1623 (Quintero-Betancourt et al, 2003;Gennaccaro et al, 2003).…”
Section: Analysis Techniques For the Evaluation Of Viabilitymentioning
confidence: 99%